Dinámica de formas inorgánicas de nitrógeno en suelos inundados de la cuenca del Río Salado: experiencia «in situ» - Quaíni, Karina Paola (2008)
In lowland river basins with agricultural activities and periodically flood events, the exchange of materials and organisms between waterlogged soil and river are significant. One century conversion of natural systems to agriculture in the Argentine Pampas has resulted in significant changes of ecological properties of the valuable freshwater ecosystems of its region. For this reason it becomes essential to know soil basin responses to flood events and its reciprocal effects on the river. The aim of this paper was to determine the nitrate (NO3 -) and ammonium (NH4 +) dynamics on soil flooded waters with different land-use and topographic position, since the flood to the dry condition. «In situ» experiences were carried out on soils from Salado River basin (Valdés, 25 de Mayo). The treatments (4x3) were made according to: land-use (agricultural ‘a’ and cattle-agricultural ‘m’) and topographic position (ridge ‘L’ and middle ridge ‘ML’). NO3 - and NH4 +, chlorophyll ‘a’ and dissolved oxygen were measured in water. According to water time permanence on each site (calculated taking into account the slope in each site) five sample times were programmed: daily in L and fortnightly in ML. In all cases NO3 - values were higher than NH4 +. Water NO3 - and NH4 + concentrations were similar in ‘a’ and ‘m’ in both topographies. According to the topography and time of water permanence, NO3 - mean values were higher for L (five days), while the opposite occurred for NH4 +. Both ions dynamics showed differences according to topography and water time permanence, but not according to land-use. These results suggested that in flooded events of lowland river basins with farming land use, the nitrogen dynamic and its transport from the soil to the flooding water have significant importance and have a direct influence on phytoplankton biomass development. The NO3 - and NH4 + dynamics were different according to water time permanence over the soil: when the flood event was for long time, the system seem to have enough time to adapt to the new conditions, and so denitrification and nitrification processes are possible; but, when the flood event is short, time is not enough for the system to adapt, and thus, nitrification and denitrification processes does not seem to occur. Considering that some authors assumed soil basin agriculture as the former responsible for the increasing nutrient concentration in the river, these results suggest that because crop-pasture, cattle lands are important in this respect and should be considered from now on.